2016
DOI: 10.1042/cs20160421
|View full text |Cite
|
Sign up to set email alerts
|

Binding of anti-dsDNA antibodies to proximal tubular epithelial cells contributes to renal tubulointerstitial inflammation

Abstract: Immune deposits are often observed along the tubular basement membrane in patients with lupus nephritis, but the role of anti-dsDNA antibody (Ab) deposition on tubulointerstitial inflammation remains to be investigated. We examined the effect of human polyclonal anti-dsDNA Abs on inflammatory processes in cultured proximal renal tubular epithelial cells (PTEC, HK-2 cells) and their association with serum levels of interleukin (IL)-6, IL-8 and monocyte chemoattractant protein-1 (MCP-1) in patients. Binding of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…The induction of these pro-inflammatory mediators is facilitated through the binding of high-mobility group box 1 protein, engagement of Toll-like receptor 2 (TLR-2) and receptor for advanced glycation end-products (RAGE), activation of the MAPK, protein kinase C (PKC), inhibitor of kappa-light chain-enhancer of activated B cells (IκB) and nuclear factor kappa B (NF-κB) signaling pathways, and endoplasmic reticulum stress 20, 3235 . Correlation between serum levels of IL-1β, IL-6, TNF-α, hyaluronan, and lipocalin and disease activity in patients with SLE further highlights the importance of these inflammatory markers in the pathogenesis of LN 17, 3639 .…”
Section: Recent Knowledge On Renal Inflammation In Lupus Nephritismentioning
confidence: 91%
See 2 more Smart Citations
“…The induction of these pro-inflammatory mediators is facilitated through the binding of high-mobility group box 1 protein, engagement of Toll-like receptor 2 (TLR-2) and receptor for advanced glycation end-products (RAGE), activation of the MAPK, protein kinase C (PKC), inhibitor of kappa-light chain-enhancer of activated B cells (IκB) and nuclear factor kappa B (NF-κB) signaling pathways, and endoplasmic reticulum stress 20, 3235 . Correlation between serum levels of IL-1β, IL-6, TNF-α, hyaluronan, and lipocalin and disease activity in patients with SLE further highlights the importance of these inflammatory markers in the pathogenesis of LN 17, 3639 .…”
Section: Recent Knowledge On Renal Inflammation In Lupus Nephritismentioning
confidence: 91%
“…The current standard-of-care induction treatments for severe LN are corticosteroids combined with either cyclophosphamide (CYC) or MPA 9699 . We have reported that MPA can exert a beneficial role on inflammatory and fibrotic processes induced by anti-dsDNA antibodies in human mesangial cells and PTECs and that this role is independent of its immunosuppressive actions 1416, 39 . We have also demonstrated that MPA together with methylprednisolone (MP) was more effective than CYC and MP in preserving renal histology with reduced severity of renal fibrosis in New Zealand black and white first-generation (NZB/W F1) mice, possibly through the ability of MPA to decrease PKC-α activation and TGF-β1 expression 15 .…”
Section: Current and Emerging Treatments For Lupus Nephritis And Theimentioning
confidence: 96%
See 1 more Smart Citation
“…Anti DNA/histone antibodies found in the kidney with lupus nephritis can promote pathogenesis by stimulating cytokine production and inflammation (61, 62). Since DNA/histone are only exposed after cell breakdown as happened in cell apoptosis or necrosis, these antibodies are unlikely to be the initiating autoantibodies in lupus nephritis.…”
Section: Anti-perlecan Antibodiesmentioning
confidence: 99%
“…While anti‐double‐stranded DNA (dsDNA) is a commonly used disease activity marker in LN, there is also data showing their active participation in pathogenic mechanisms that involve interactions with resident renal cells. Data from our group showed that the binding of anti‐dsDNA to proximal renal tubular epithelial cells induced the cells to adopt a more mesenchymal morphology and transform into pro‐inflammatory and pro‐fibrotic phenotypes . Data from animal and in vitro studies also showed that mycophenolic acid treatment could attenuate these cellular changes and suppress relevant pro‐inflammatory cytokine pathways, thus suggesting direct effects of treatment on renal inflammation distinct from the immunosuppressive actions of the drug …”
Section: Recent Insights On Pathogenesis From Histopathology and Tranmentioning
confidence: 96%